Effect of Ozonated Olive Oil in Topical Application towards Osteoblast Number and Angiogenesis of Alveolar Bone in Periodontitis Healing Process (in vivo study in Sprague dawley Rats) - Dahlia Herawati; Deassy Anggraeni; Ariska Ratih Damayanti (Faculty of Pharmacy, Universitas Gadjah Mada, 2020)
Ozonated olive oil has been widely used as a local infection therapy to overcome bacterial resistance from antibiotics with systemic administration. However, the disadvantage of systemic antibiotics is it cannot be used in large doses for local infection therapy. Periodontitis is an infectious disease that causes alveolar bone damage. In the periodontitis healing process, osteoblasts and angiogenesis play essential roles in bone regeneration. The study aims to determine the effect of topical application ozonated olive oil to osteoblasts number and angiogenesis of alveolar bone in periodontitis healing process using in vivo study. 32 Sprague Dawley rats were divided into two groups: the treatment and placebo groups, 16 rats in each group. The induction of periodontitis was performed by ligating lower incisor with silk ligature for seven days. The treatment group received ozonated olive oil, and the placebo group received 1 % of CMC-Na twice a day. Four rats from each group were necropsied on day 3, 5, 7, and 14 and then processed into histological sample preparations by hematoxylin-eosin staining and counted the number of osteoblast and blood vessels. All collected data were analyzed using two-way ANOVA and posthoc LSD test. The average number of osteoblasts, blood vessels in the treatment group were significantly higher than the placebo group (p <0.05) either on day 3, 5, 7, and 14. Results showed the ozonated olive oil increase the regeneration of alveolar bone in the periodontitis healing process in Sprague Dawley. Therefore ozonated olive oil has the effect of periodontal tissue regeneration.